Performa Pertumbuhan Benih Ikan Gurami (Osphronemus gouramy) Dengan Pemberian Pakan Komersil yang Ditambahkan Tepung Daun Gamal (Gliricidia sepium) Terfermentasi - Fitria Apriani; Eva Prasetiyono; Denny Syaputra (Faculty of Science and Technology University Ibrahimy, 2019)
Gouramy is freshwater fish commodity with higher market demand than other freshwater fish that mostly cultured. There are many obstacles in cultivating process i.e the slow growth and the increasing of feed price that is not automatically followed by the increasing of the fish price causing the efforts to decrease the feeding cost are urgently needed. The aims of this study were to evaluate the effect of fermented gamal leaf addition into commercial feed to the growth of gouramy fry. The design of experiment using completely randomized design with 4 levels of treatment and 3 replicates each. The result showed that the addition of fermented gamal leaf into commercial feed gives a significant effect to growth of the fry. The mix of 75% gamal leaf and 25% commercial feed is able to decrease the using of commercial feed